Long‐term outcome and mode of recurrence following noninducibility during noninvasive programmed stimulation after ventricular tachycardia ablation. Issue 3 (31st January 2019) - Shirai, Yasuhiro; Liang, Jackson J.; Santangeli, Pasquale; Arkles, Jeffrey S.; Schaller, Robert D.; Supple, Gregory E.; Lin, David; Nazarian, Saman; Deo, Rajat; Dixit, Sanjay; Epstein, Andrew E.; Callans, David J.; et al.
Abstract: Background: Noninducibility of ventricular tachycardia (VT) at noninvasive programmed stimulation performed shortly following ablation (negative NIPS) predicts low risk of the medium‐term recurrence. This study aimed to evaluate long‐term rate and mode of recurrence following negative NIPS. Methods: We extended follow‐up on patients in whom no VT could be induced at NIPS following ablation between 2008 and 2010. Recurrent VTs were categorized as "Original clinical" if they matched VT that had occurred spontaneously prior to the index ablation; "Original nonclinical" if they matched VT that was induced during the index ablation but had not occurred spontaneously; or "New." Among those undergoing repeat ablation, the area ablated to treat the recurrent VT was categorized as "Targeted initial scar" if it was targeted during the index procedure; "Untargeted initial scar" if it was present but not targeted during the index procedure; or "New scar" if it was not present during the index procedure. Results: Of 60 patients with negative NIPS, 18 (30%) had recurrent VT and nine underwent repeat ablation over (4.1 ± 3.2) years follow‐up. Of 23 recurrent VTs, 18 (78%) were "New." During repeat ablations, six (46%) of the 13 recurrent VTs were ablated in "untargeted initial scar" and four (31%) in "new scar." Conclusions: When spontaneous or inducible VTs are eliminated with ablation and no longer inducible during NIPS, these VTs are unlikely to recur during long‐term follow‐up. More commonly, new VTs occur, which are either associated with areas of scar not present or not targeted during the initial ablation.